2003
DOI: 10.3748/wjg.v9.i12.2642
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant crypt foci as microscopic precursors of colorectal cancer

Abstract: Since the first detection of aberrant crypt foci (ACF) in carcinogen-treated mice, there have been numerous studies focusing on these microscopically visible lesions both in rodents and in humans. ACF have been generally accepted as precancerous lesions in regard to histopathological characteristics, biochemical and immunohistochemical alterations, and genetic and epigenetic alterations. ACF show variable histological features, ranging from hyperplasia to dysplasia. ACF in human colon are more frequently locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 86 publications
5
91
1
14
Order By: Relevance
“…Aberrant crypt foci (ACF) are putative precursors of colon cancer. 35 They are considered to be surrogate biomarkers of colon cancer, particularly for the screening of chemopreventive agents. Therefore, ACF count was used as a surrogate marker in our bioassay.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant crypt foci (ACF) are putative precursors of colon cancer. 35 They are considered to be surrogate biomarkers of colon cancer, particularly for the screening of chemopreventive agents. Therefore, ACF count was used as a surrogate marker in our bioassay.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed review of the molecular features of ACF can be found in the papers by Cheng and Lai [12] and Alrawi et al [14] , and recent advances in human ACF and their potential as biomarkers of human colorectal cancer have been elegantly discussed by Orlando et al [15] , Stevens et al [16] and Gupta et al [17] . Depending on their growth/ developmental stage, ACF are heterogeneous in their molecular make-up [12][13][14] . The growth and development of ACF on one hand could be regressed or inhibited, while on the other augmented by various compounds; both depend on the ACF dynamics as well as their heterogeneity [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, in the course of their dynamics, ACF undergo several genetic changes, plausibly acquire novel phenotypes conducive to their progression, and discard those that render them normal or make them susceptible to regression [12,13] . Detailed review of the molecular features of ACF can be found in the papers by Cheng and Lai [12] and Alrawi et al [14] , and recent advances in human ACF and their potential as biomarkers of human colorectal cancer have been elegantly discussed by Orlando et al [15] , Stevens et al [16] and Gupta et al [17] . Depending on their growth/ developmental stage, ACF are heterogeneous in their molecular make-up [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig, 1A and B, gross appearance of colon showing large multiple tumors in cortical neurons transplanted animals but show a small size tumor in BEP neuronal treated animals. ACF are pre-neoplastic lesions that serve as biomarkers for colon cancer (15,18). Aberrant crypts stain heavily with methylene blue and are larger than normal crypts and have characteristic elliptical shape and thickened epithelial lining (Fig.…”
Section: Resultsmentioning
confidence: 99%